KONTROVERSI ISU NEPOTISME KHALIFAH UTSMAN BIN AFFAN - Azis Faturokhman; Is Nurhayati (STAI ALHIKMAH Jakarta, 2022)
AbstractUtsman bin Affan was famous as fair chalif and had many achievements during his tenure as chalif. Howefer, all the virtues and achievements during his caliphate seemed to disappear because of his controversial policies. The circulating issues, especially the issue of nepotism caused a rebellion that ended in the death of caliph Utsman bin Affan. Ironically, orientalist historians and some Muslim historians in their writings later branded Utsman bin Affan as the first person to practice nepotism in the history of Islamic civilization. This study aims to explore Utsman bin Affan’s policies were the root of the isu nepotism in his time. This study uses library research to provide and overview of the nepotism controversy during the caliphate of Utsman bi Affan. At the time of caliph Utsman, the issue of nepotism was blowing hard when the rebels accused Utsman bin Affan of firing a number of officials and replacing them with relatives who did not have the ability and capacity to lead the Muslims. As for giving positions to relatives accompanied by considerations of competence, professionalism and trustworthiness, it is not prohibited in Islam. AbstrakUtsman bin Affan dikenal sebagai khalifah yang adil dan banyak memiliki prestasi selama menduduki kursi khalifah. Namun, semua keutamaan dan prestasi selama masa kekhalifahannya seakan sirna karena kebijakannya yang dianggap kontroversial. Isu-isu yang beredar terutama isu nepotisme menyebabkan terjadinya pemberontakan yang berakhir dengan kematian Khalifah Utsman bin Affan. Ironisnya para sejarawan orientalis dan beberapa sejarawan muslim dalam tulisannya kemudian mencap Utsman bin Affan sebagai orang pertama yang melakukan praktik nepotisme dalam sejarah peradaban islam. Penelitian ini bertujuan mengupas lebih dalam kebijakan-kebijakan Utsman bin Affan yang menjadi akar isu nepotisme di masanya. Penelitian ini menggunakan library research untuk memberikan gambaran umum tentang kontroversi nepotisme pada masa kekhalifahan Utsman bin Affan. Di masa Khalifah Utsman isu nepotisme ini berhembus kencang ketika para pemberontak menuduh Utsman bin Affan memecat sejumlah pejabat dan menggantinya dengan kerabat yang tidak mempunyai kemampuan dan kapasitas untuk memimpin kaum muslimin. Adapun memberikan jabatan kepada kerabat yang disertai dengan pertimbangan kompetensi, profesionalisme dan sifat amanah, maka tidak dilarang dalam Islam.